Indicadores de fragilidade à erosão no apoio à definição de áreas de preservação permanente em rios - Monteiro, Josita Soares (2014)
The protection of watercourses is motivated by legal instruments establishing permanent preservation areas (PPAs) along them, being defined from the width of the waterway. However, it is believed that there are other factors to consider, such as ecosystem services offered by PPAs. With the objective of developing a methodology for easy application that supports the identification of ecosystem services promoted by APPs along watercourses, in particular the stability of river embankments, this study developed a Rapid Assessment Protocol (RAP), compound for 7 parameters - vegetation, soil texture, stretch of river, slope inclination, soil depth in slope, width of the stream and, use and land cover, assigning them weights 0-4, depending on influence of their categories in the susceptibility to erosion of river embankments. The RAP was applied in 40 sampling units in the watershed of the Arroio Val de Buia, in Silveira Martins, RS. The end result of the RAP for each sample unit allowed the creation of classes of susceptibility to erosion, "stable", "susceptible" and "unstable". Simultaneously, we developed an algorithm programming in Python 2.6 (ArcGIS ® 10) language in order to determine indicators of fragility erosion of slopes of the watercourse areas and the contribution of these in susceptibility to erosion of river embankments. Statistical analysis (t test) revealed significant differences between the units evaluated by RAP. From the techniques of Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA), we observed the occurrence of clustering between different sampling units into two distinct classes, according to the categories of susceptibility to erosion resulting RAP. The basic parameters that determine the groupings were: soil, soil depth on slope, vegetation, portions of the stream and use and land cover. The PCA also showed that the first principal component (PC1) explained 43.54 % of the total variance, while the second explained 25.93 %, which showed the similarities between the "stable" sample units and "unstable", respectively. For indicators of fragility to erosion, the following information was obtained: maximum length of the tributary side, average steepness of maximum length side, accumulated tributary drainage area, average steepness of the cumulative tributary drainage area and, average velocity of maximum length side. The contribution of indicators of fragility in susceptibility to erosion of river embankments can be enhanced or attenuated depending on the category of the parameters evaluated in the RAP. It also pointed out that one of the products of this work was the algorithm programming that originated maps on indicators of fragility erosion down slope. Finally, it is concluded that the proposed protocol was presented as a good tool for rapid assessment of rivers with similar characteristics to Arroio Val de Buia, and useful for zoning and hierarchy of priority areas for environmental management and recovery degraded areas, especially those related to works of natural engineering, may be disseminated and applied, provided to regional characteristics.